Building Capacity For Innovation Through R&D Consortia in Health Projects: From Network Interaction to Systemic Transformation - Ria Hardiyati; Trina Fizzanty; Erman Aminullah (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
This paper attempt to elucidate the postulation that there is a continuous trajectory from the network interaction in scientific research towards the systemic transformation in innovation capacity building. This study will expose that the availability of research capacity in certain areas can be developed into innovation capacity through R&D consortia, where building research capacity is a long term process of scientific accumulation. This study utilizes two techniques scientometrics and case study in stem cell and vaccine research in understanding innovation capacity.The research capacity in the area of vaccines has been long started from individual research conducted by researcher. It has been continued into organization research, and then developed into building innovation capacity through R&D consortia. However, in areas of stem cell there is still lack of evidence but it directly leaps to build innovation capacity through R&D consortia. Therefore further empirical evidence is needed to support the continuous trajectory.